Unusual products in the reactions of phosphorus(III) compounds with N=N, C equivalent to C or conjugated double-bonded systems - Swamy, K. C. Kumara; Balaraman, Ekambaram; Pavan, M. Phani; Kumar, N. N. Bhuvan; Kumar, K. Praveen; Kumar, N. Satish (Journal of Chemical Sciences, 2006)
The diversity of products in the reaction of diethyl azodicarboxylate (DEAD)/diisopropyl azodicarboxylate (DIAD) and activated acetylenes with PIII compounds bearing oxygen or nitrogen substituents is discussed. New findings that are useful in understanding the nature of intermediates involved in the Mitsunobu reaction are highlighted. X-ray structures of two new compounds (2-t-Bu-4-MeC6H3O)P (μ-N-t-Bu)2P+[(NH-t-Bu)N[(CO2]-i-Pr)(HNCO2-i-Pr)]](Cl-)(2-t-Bu-4-MeC6H3OH)(23)and [CH2(6-t-Bu-4-Me-C6H2O)2P(O)C(CO2Me)C-(CO2Me)CClNC(O)Cl] (33) are also reported. The structure of23 is close to one of the intermediates proposed in the Mitsunobu reaction.

Unprecedented catalytic hydrogenation of urea derivatives to amines and methanol - Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Indirekte CO2-Hydrierung: Eine Hydrierung von Harnstoffen zu Aminen und Methanol (siehe Bild) wird durch einen RuII-Pinzettenkomplex mit dreizähnigem bipyridinbasiertem PNN-Liganden katalysiert und verläuft unter milden, neutralen Bedingungen bei einem H2-Druck von 13.6 atm. Da sich Harnstoffderivate ausgehend von CO2 erhalten lassen, ermöglicht dieser Ansatz die indirekte Hydrierung von Kohlendioxid zu Methanol.

Use of ruthenium complexes for formation and/or hydrogenation of amides and related carboxylic acid derivatives - Milstein, David; Gunanathan, Chidambaram; Ben-David, Yehoshoa; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Zhang, Jing (US20120253042, US20160152663, 2012)
A process for preparing amides by reacting a primary amine and a primary alcohol in the presence of a Ruthenium complex to generate the amide and molecular hydrogen. Primary amines are directly acylated by equimolar amounts of alcohols to produce amides and molecular hydrogen (the only byproduct) in high yields and high turnover numbers. Also disclosed are processes for hydrogenation of amides to alcohols and amines; hydrogenation of organic carbonates to alcohols; hydrogenation of carbamates or urea derivatives to alcohols and amines; amidation of esters; acylation of alcohols using esters; coupling of alcohols with water and a base to form carboxylic acids; dehydrogenation of beta-amino alcohols to form pyrazines and cyclic dipeptides; and dehydrogenation of secondary alcohols to ketones. These reactions are catalyzed by a Ruthenium complex which is based on a dearomatized PNN-type ligand of formula A1 or precursors thereof of formulae A2 or A3.

Unified strategy for silver-, base-, and oxidant-free direct arylation of C-H bonds - Sahoo, Manoj K.; Midya, Siba P.; Landge, Vinod G.; Balaraman, Ekambaram (Green Chemistry, 2017)
Here, we report a dual catalytic approach for room temperature direct arylation of C-H bonds with aryldiazonium salts as a simple aryl group donor, also working as an internal oxidant via C-N-2 bond cleavage. This unified strategy has been achieved by the synergistic combination of visible-light metal-free photoredox and palladium catalysis under silver-, base-and/or additive-free conditions. The broad substrate scope, functional group tolerance, excellent regioselectivity and redox-neutral conditions of this process make it attractive for the effective synthesis of a wide range of important N-heterocyclic commodities such as dibenzo [b,d]azepine, carbazole and phenanthridine.